The Implications of the Countercyclical COVID-19 Policy on the Performance of Rural Banks and Sharia Rural Banks in Indonesia - Syukri Iska; Nofrivul Nofrivul; Indra Jaya; Ifelda Nengsih; Elsy Renie (JURIS (Jurnal Ilmiah Syariah), 2024)
This study investigated the impact of the Indonesian government policies implemented through POJK No. 11/POJK.03/2020 on the banking performance of Rural Bank (BPR) and Sharia Rural Bank (BPRS) after the implementation of countercyclical policies to stimulate the country's economy affected by the COVID-19 pandemic in Indonesia between March and December 2020. Mixed method approaches were applied to analyze the contributing factors to different performances between seven Rural Banks and seven Sharia Rural Banks in West Sumatra that were randomly selected through purposive sampling based on proportionate assets.  The quantitative data were financial statements sourced from the OJK 2021 Publications, and the qualitative data were collected from in-depth interviews with eight Directors of Rural Banks and Sharia Rural Banks selected from the snowball sampling. Analyzing Indonesian government policies embodied in the countercyclical policy, we found that banking policies in Sharia Rural Banks outperformed those of conventional Rural Banks, as reflected by the average ROA (1.16% vs 1.33%), ROE (0.09% vs. 0.08%), and NPL (6.67% vs. 6.82%). The contributing factor to this gap was the different internal policies of each institution to translate the countercyclical concept based on the operational principles, such as the interest rate of Rural Bank and margin of Sharia Rural Bank despite the fact that both banks shared practice in the principal deferment and credit extension.